Ministerio fiscal y división de poderes - Sendín García, Miguel (Universidad Nacional del Litoral, 2017)
This article critically examines the legal framework of the prosecutor, reflecting on its correct articulation, and especially questioning whether it has an appropriate degree of autonomy to develop its functions.